P-83 Carry on caring: structured carer support. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Birch, Helen; Ainsworth, Catherine; Webster, Laura
Abstract : Background: The multi-professional team identified the need to provide a more structured programme of support for carers. Aim: To provide a bespoke programme of support and advice to carers of patients from any services provided across the organisation, based on requirements following individual holistic assessment. This would be delivered either in a group setting or individually as appropriate. Methods: Carers were identified and the carers programme was explained to them with an invitation to attend for a personal carer's assessment. The programme is co-ordinated by the Day Services Sister. A five-week programme is implemented, with approximately six carers attending one day a week for five consecutive weeks. Carers from patients on the inpatient unit were often unable to complete the programme but were encouraged to attend when possible. Carers accessed therapy services, social worker was available for support and advice, catering staff provided information about nourishing the whole person. Hand massage and anxiety management sessions were provided as is lunch. Care shifts were provided for patients at home by Queenscourt at Home thus enabling the carers to attend. Conclusion: Evaluations have exceeded expectations. We expected carers to be disappointed when the programme ended, however, many of them have formed support groups of their own and arranged to meet regularly. Carers feel empowered with more knowledge and skills, and many realise that taking time out for themselves should be seen as a necessity and not a guilty pleasure. Other comments include ' don't feel so alone any more ' and ' I feel well cared for myself' . We will continue to run the programme and adapt it as necessary according to evaluations.